Penyebab Anak Putus Sekolah (Studi Kasus di Sanggar Kegiatan Belajar, Kecamatan Jambi Selatan, Kota Jambi) - Agustin, Amalia; Salam, Muhammad; Utami, Sundari (Journal of Civic Education, 2024)
This study investigates the determinants of school dropout among children in South Jambi District and proposes strategies to address this issue. Conducted at the Sanggar Kegiatan Belajar (SKB) in South Jambi District, Jambi City, the qualitative descriptive research employed observation, interviews, and documentation as data collection methods. Informants included school dropouts, their parents, the Non-Formal Education Division's secretary, and SKB tutor teachers. Data analysis entailed data reduction, display, and verification. Findings revealed that school dropout stems from factors such as children's lack of interest, discomfort at school, academic difficulties, and parental regret over discontinuing their child's education. Additionally, environmental, parental, and economic factors emerged as prominent causes, while peer influence also played a role, with non-school-going friends discouraging attendance. Educational authorities and SKBs respond with interventions including teaching core subjects, skills development, and empowerment initiatives to reignite students' enthusiasm for learning. The study underscores the importance of parental, school, and governmental support to prevent school dropout and implement effective interventions.